PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN (STUDI KASUS: PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX) - Nur Fitri Eka Asbarini; Salmi Yuniar Bahri (BADAN PENERBIT STIEPARI PRESS, 2022)
In this study, it was conducted to test the relationship or influence of profitability, company size, and debt policy on the value of companies that were entirely listed on the Jakarta Islamic Index (JII) during the 2019 period. The model of analysis techniques used in this study is multiple regression analysis. The dependent variables are the value of the company and the independent variables are profitability, company size, and debt policy. The result in this study is that only the profitability variable is explained with the ROA proxy which has a significant positive effect on the company value variable described with the PBV proxy, while the company size variable and debt policy have no effect on the dependent variable.